Geochemical Characteristics of Bintuni Oil Seep, Oil-Oil Correlation, and Oil-Source Rock Correlation Using Biomarker Data in The Bintuni Basin, West Papua - Eriko Sabra; Hanif Mersil Saleh (Scientific Contributions Oil and Gas, 2025)
This study conducts a geochemical analysis of oil seepage and its correlation with existing oil and source rock. Biomarker analysis indicates that the Bintuni oil seep likely originates from a Tertiary source rock deposited in a transitional environment under sub-anoxic conditions, with a dominant terrestrial input and experienced slight biodegradation. The sample exhibits Pr/Ph values of 1.48 and 1.49, a dominance of C29 sterane, diasteranes/steranes ratios of 0.83 and 0.84, C29/C30 hopane ratios of 0.39 and 0.43, homohopane indices of 0.01 and 0.02, and high oleanane indices of 0.69 and 0.61. Oil to oil correlation reveals that the Bintuni oil seep is correlated with oil from the Salawati Basin and the Manimeri oil seep. The common characteristics among these three samples include the presence of oleanane, kerogen type II/III, Pr/Ph ratio, and redox conditions. However, differences are observed in the dominant material input: the Bintuni oil seep is dominated by C29, whereas Salawati oil exhibits a balanced C27-C28-C29 ratio, and Manimeri Oil Seep is dominated by C27. Correlation with the Ofaweri-1 oil stain in the Bintuni Basin indicates similarities in the dominance of C29. However, differences exist in the oleanane index and salinity, as the Bintuni oil seep has a higher oleanane index and lacks of gammacerane. Oil to source rock correlation suggests that the Bintuni oil seep shares characteristics with samples from the Klasafet Formation, including type II/III kerogen, a land-plant source, the absence of gammacerane, high oleanane content, and similarly high C29 values. The difference between these two samples lies in the values of tricyclic terpanes, Pr/Ph value, and the oxidizing conditions. The Bintuni Oil Seep has lower tricyclic terpane values, lower Pr/Ph value, and was deposited under more anoxic conditions. The similarity in characteristics with several Tertiary oils and the Klasafet Formation indicates that the Bintuni oil seep likely originates from the Klasafet Formation.